Hellenistic and Roman Sparta - Cartledge, Paul, author. (London)
1 online resource (318 pages)
Keywords: This original and compelling account of later Spartan history challenges the conventional misperception of Spartan 'decline' after the loss of her status as a great power on the battlefield in 371 BC.